Necesidad de determinar la responsabilidad civil, y administrativa de los funcionarios o empleados de los gobiernos autónomos descentralizados, (gad) por conceder permisos de construcción, en zonas no aptas - Mendoza Piedra, Luis Eduardo (2015)
The State has the power to sanction illegal behavior different; the criminality has among its purposes to maintain a social order, criminal law is a legal science both objective and subjective, the Ius puniendi is the power of the state to punish , therefore the law is not a doctrine but a peaceful mechanism make rules to keep them alive and operating them for the benefit of all people to protect by law the basic legal rights. At present there is no civil, criminal or administrative sanction to punish officials or city employees who provide building permits in unsuitable areas The evolution of criminal law has enabled us to ensure legal rights for individuals and the right to punish. Prior to introduction to the proposed topic, deign to remember that the science of criminal law, the crime studying the complexity of its elements and consequences. Considered not as a simple antagonistic relationship between an act and a legal norm appreciate it as a human fact, individual and social. His research therefore are oriented in the direction of attaining knowledge of the crime in its double aspect; objective and subjective. So the criminal law should forewarn the legal rights guaranteed by the Constitution and international instruments, through civil, criminal or administrative officials for authorizing construction in areas not suitable penalties. The Ecuadorian State has as one of its objectives the provision of public goods and services, to the effect, collects different types of taxes and contributions, the same as part of the general budget of the State for the provision of goods and services public. So its services must be efficient and effective as well as responsibility.